2011
DOI: 10.1590/s0066-782x2011005000105
|View full text |Cite
|
Sign up to set email alerts
|

Função endotelial vascular em pacientes com fluxo coronário lento e os efeitos do nebivolol

Abstract: Background: Brachial endothelial function has been associated with coronary slow flow (CSF). Increasing blood flow to brachial artery provokes endothelium to release nitric oxide (NO) with subsequent vasodilatation. Besides its β1-blocker activity, nebivolol causes vasodilatation by increasing endothelial NO release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A recent study showed that aspirin did not improve brachial flow-mediated dilatation (FMD), an index of endothelial function in patients with SCF. However, patients treated with aspirin were free of angina after treatment of SCF [35]. In this study, use of aspirin was significantly higher in the SCF group than the control group.…”
Section: Discussionmentioning
confidence: 67%
“…A recent study showed that aspirin did not improve brachial flow-mediated dilatation (FMD), an index of endothelial function in patients with SCF. However, patients treated with aspirin were free of angina after treatment of SCF [35]. In this study, use of aspirin was significantly higher in the SCF group than the control group.…”
Section: Discussionmentioning
confidence: 67%
“…Based on these three previous studies, the pathophysiological mechanism of CSF is still unclear and it seems impossible to explain the CSF process by only one mechanism. However, among all the suggested underlying mechanisms, endothelial dysfunction is the most widely recognized [ 13 15 ]. Meanwhile, numerous studies have indicated that miRNA-22 plays a key role in regulating endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of miRNAs in CSF is still not clear. Although the pathophysiological mechanism of CSF remains unclear, endothelial dysfunction is widely considered to play an important role [ 13 15 ]. Numerous studies have indicated that miRNA-22 plays a key role in regulating endothelial function [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ischemic coronary artery diseases typically have coronary artery stenosis, although approximately 10–20% of patients with angina pectoris have normal coronary artery, and most of these patients are syndrome X that showed slow coronary flow [1], [2]. In addition, patients with chest pain but with an intact coronary artery stenosis were reported [3], [4].…”
mentioning
confidence: 99%